Longitudinal Cross-Lagged Analysis Between Depressive Symptoms, Social Withdrawal, Self-Esteem, and School Adaptation in Multicultural Adolescents - Chung Choe; Seunghee Yu (Psychologica Belgica)
In Korea, as the number of multicultural families formed through the marriage of Korean men and foreign women from lower-income countries such as China, Southeast Asia, and Central Asia increases, the psychosocial adaptation of adolescents from these families is becoming increasingly important. This study examines the longitudinal and reciprocal relationships among depressive symptoms, social withdrawal, self-esteem, and school adaptation in multicultural adolescents in high schools. We applied an autoregressive cross-lagged model to a sample of 594 multicultural adolescents extracted from three consecutive years of data from the Multicultural Adolescents Panel Survey and found that depressive symptoms and school adaptation had reciprocal negative relationships in multicultural adolescents’ first and second years of high school. In these years, while higher school adaptation led to lower social withdrawal, social withdrawal did not affect school adaptation. In the second and third years of high school, self-esteem and school adaptation had a reciprocal positive relationship. Females had more severe psycho-emotional problems than males. Child neglect increased the risk of depressive symptoms and social withdrawal while lowering self-esteem. A high household income was associated with lower social withdrawal. Adolescents in urban areas exhibited higher levels of depressive symptoms, lower self-esteem, and poorer school adaptation compared to those in rural areas. These results imply that reducing parents’ neglect of their children is necessary to alleviate depressive symptoms and school maladaptation among multicultural adolescents. Moreover, financial support for multicultural adolescents in their learning can improve school maladaptation and reduce social withdrawal.